Leadership Strategy of the School Principal in Improving the Quality of Education in Remote Areas - Yukinta Nasya Berty; Putu Sudira; Maulina Idami Alim (Universitas Ahmad Dahlan, 2026)
This study aims to analyze the leadership strategy of the school principal in improving the quality of education in remote areas, specifically at SMKN 12 Sarolangun. Remote areas often face various challenges in accessing quality education, such as limited infrastructure, minimal government support, and low community participation in education. Therefore, the role of the school principal is crucial in creating an environment that supports the improvement of education quality in these areas. This research employs a qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. Participants in this study include the school principal, teachers, and other relevant stakeholders involved in the educational process at SMKN 12 Sarolangun. The collected data were analyzed using thematic analysis techniques to identify and describe the various leadership strategies implemented by the principal in addressing the existing challenges and efforts to enhance the quality of education. The results show that the principal at SMKN 12 Sarolangun applies several leadership strategies, including human resource development, improving the quality of teaching and learning, and utilizing technology and networking with external parties. In addition, the principal is also active in building partnerships with the community and related agencies to support educational activities at the school. This research is expected to make a significant contribution to the development of educational leadership strategies in remote areas and serve as a reference for other school principals in efforts to improve education quality in similar conditions.